Toward Improving the Design of Sustainability Standards—A Gendered Analysis of Farmers' Preferences. (November 2017) - Meemken, Eva-Marie; Veettil, Prakashan Chellattan; Qaim, Matin
Highlights: Choice experiment to analyze farmers' preferences for sustainability standards. Gender-disaggregated data from smallholder coffee growers in Uganda. Farmers have positive attitudes toward sustainability standards in general. They dislike bans of chemical inputs; prefer schemes with training and female support. Preferences vary by gender, but female support is appreciated by men and women. Summary: Recently, sustainability standards have gained in importance for export crops produced in developing countries. Several studies analyzed whether such standards deliver on their promise to improve the livelihoods of poor farmers, with mixed results. Here, we ask whether the design of standards could be improved such that farm households benefit more. An assessment of what particular features of standards hamper or facilitate participation requires a better understanding of farmers' preferences. Our contribution is twofold: First, based on a choice experiment we analyze how farmers evaluate actual and hypothetical features of standards. Data were collected from small-scale coffee producers in Uganda. Second, this is the first quantitative study on standards employing a gendered research design. A gender focus is important, because coffee and other certified export crops are often controlled by men. The choice experiment included features of standards aimed at reducing gender inequality and was conducted separately with male and female members of farm households. Results indicate that farmers have positive attitudes toward sustainability standards in general. While they dislike bans of productivity-enhancing inputs, agricultural training and special female support are appreciated. Many also see requirements that have to be met for certification as a welcome nudge to invest in better farm management and quality upgrading. Female farmers have a higher preference for standards than male farmers. Also within households, significant preference heterogeneity between women and men is found.